2019
DOI: 10.3390/cells8070685
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Molecular Knowledge of Therapeutic Drugs and Natural Products Focusing on Inflammatory Cytokines in Asthma

Abstract: Asthma is a common respiratory disease worldwide. Cytokines play a crucial role in the immune system and the inflammatory response to asthma. Abnormal cytokine expression may lead to the development of asthma, which may contribute to pathologies of this disease. As cytokines exhibit pleiotropy and redundancy characteristics, we summarized them according to their biologic activity in asthma development. We classified cytokines in three stages as follows: Group 1 cytokines for the epithelial environment stage, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 184 publications
(186 reference statements)
0
25
0
1
Order By: Relevance
“…Lin et al divided asthma-related cytokines into three stages, firstly the epithelial environment stage, secondly the Th2 polarization stage, and finally the tissue injury stage, in which ILQ is mainly aimed at the second stage and inhibits the secretion of inflammatory factors by Th2 cells. 54 The effects of ILQ on airway inflammation in the murine asthma model have not been previously reported. ASHMI, like most traditional Chinese medicines, has a typical problem of poor patient compliance due to its large dose and difficulty in dissolution, so we tried to prepare the ILQ-SMEDDS to improve compliance of asthma patients.…”
Section: Ilq-smedds Markedly Suppressed the Inflammatory Cell Counts mentioning
confidence: 98%
“…Lin et al divided asthma-related cytokines into three stages, firstly the epithelial environment stage, secondly the Th2 polarization stage, and finally the tissue injury stage, in which ILQ is mainly aimed at the second stage and inhibits the secretion of inflammatory factors by Th2 cells. 54 The effects of ILQ on airway inflammation in the murine asthma model have not been previously reported. ASHMI, like most traditional Chinese medicines, has a typical problem of poor patient compliance due to its large dose and difficulty in dissolution, so we tried to prepare the ILQ-SMEDDS to improve compliance of asthma patients.…”
Section: Ilq-smedds Markedly Suppressed the Inflammatory Cell Counts mentioning
confidence: 98%
“…9 -11 The inhalation of glucocorticoid is widely used; however, it is well-known that the long-term use of high dose can cause side effects, such as bone loss, insulin resistance, and predisposition to diabetes. 11…”
Section: Introductionmentioning
confidence: 99%
“…This kinase is directly activating the transcription factor NF-ÎșB, thus representing a good therapeutic target with possible less side effects than upward kinases, in particular MAP kinases [ 2 ]. Asthma is a common inflammatory respiratory disease spread worldwide [ 31 ]. Our previous study in a mouse model of asthma showed that one of the available inhibitors of MSK1, H89 , significantly inhibits the eosinophil recruitment in bronchoalveolar lavage [ 14 ].…”
Section: Discussionmentioning
confidence: 99%